2018
DOI: 10.1111/1750-3841.14095
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Preference and Perception of Freshness in Roasted Peanuts (Arachis spp.) for European Consumers

Abstract: This study provides insight into which flavor, taste, and appearance attributes drive liking and disliking of roasted peanuts for European consumers. The drivers are linked back to analytical attributes that can be measured instrumentally, thereby reducing the reliance on costly sensory panels. Particular emphasis is placed on color as a predictor of preference, because of the low cost of the measuring equipment, it is available to even smaller producers. In addition to preference, the study also examines whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…On the contrary, a negative correlation was observed between consumers overall liking and pyrazines, bitterness, astringency, and woody and burnt flavor notes. Similar results were also reported for roasted peanuts revealing that the consumers drivers of liking were even similar across different countries (Spain, Netherlands, and Turkey), with color, sweetness, roasted peanut parameters increasing the liking and the contrary for bitterness (Lykomitros et al., 2018).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…On the contrary, a negative correlation was observed between consumers overall liking and pyrazines, bitterness, astringency, and woody and burnt flavor notes. Similar results were also reported for roasted peanuts revealing that the consumers drivers of liking were even similar across different countries (Spain, Netherlands, and Turkey), with color, sweetness, roasted peanut parameters increasing the liking and the contrary for bitterness (Lykomitros et al., 2018).…”
Section: Resultssupporting
confidence: 77%
“…Simultaneously, a * , b * , and C * increased inside the kernel, implying a more intense and brownish (mix of red and yellow color coordinates) color as result of increasing roasting temperature. The decrease in L * values and increase in a * values were previously also reported in roasted peanuts and the phenomenon was related to the higher melanoidin production from Maillard reactions and with a lower finished moisture content (Lykomitros, Fogliano, & Capuano, 2018). However, the outside color was characterized by lower values of a * , b * , and C * which meant that red and yellow notes decreased in the almond skin exposed to the highest temperature, 190 °C.…”
Section: Resultssupporting
confidence: 68%
“…In another study, Lykomitros et al [64] reported that roasted peanut, dark roast and sweet aromas, and sweet taste were the drivers of liking, while raw bean aroma and bitter taste were detractors for the liking of roasted peanut for European consumers. Kim et al [23] studied sensory profiles of commercial orange juice products in the Korean market using a lexicon with 23 descriptors, and identified drivers of liking of Korean consumers.…”
Section: Applications Of Lexiconsmentioning
confidence: 99%
“…In addition, the solid nature of nut samples makes their agitation difficult, and the addition of water is necessary for homogenization purposes [ 22 ]. Moreover, some researchers increased the medium ionic strength in order to modify the nature of the matrix and the extraction efficiency, since this addition could affect the partition coefficient of the analytes [ 25 , 26 ]. Nevertheless, the higher the ionic strength, the lower the solubility of neutral molecules in water and the less likely these molecules are to pass from the solid matrix to the water.…”
Section: Analysis Of Vocs Present In Nutsmentioning
confidence: 99%